Anticipatory access to group-level information in working memory. Issue 11 (November 2018) - Farrell, Simon
One assumption common to many serial recall models is that lists can be stored in a structured manner, as groups nested inside larger sequences. However, many of these theories fail to explain the dynamics by which those groups are accessed, and those models that do provide such an account have not been comprehensively tested. This article presents three experiments using a probed recall paradigm in which potential target positions were precued. Across all the experiments, it was found that a precue that targeted only a single group led to faster recall than one that targeted multiple groups, in cases where the number of positions precued was equated. In two of the three experiments, there was evidence (quantified using Bayes factors [BFs]) that responding under a precue targeting multiple groups was no faster than an uniformative control precue. The results suggest that retrieval of groups is a major bottleneck to recall items in structured lists and are consistent with models assuming that information about groups is retrieved prior to accessing elements in the groups themselves.